Implementasi Program “Ayo Cegah Stunting” di Kampung Koceak, Setu, Tangerang Selatan - Widiah Nur Halimah; Aulia Arafah; Anita Rahmaan; Novielda Rahmadania; Mulkan Habibi (Communio: Jurnal Pengabdian Kepada Masyarakat, 2023)
Maternal and child health services during the Covid-19 pandemic have been severely impacted. A quick survey conducted in June 2020 showed that 75% of posyandu in Indonesia did not provide services due to the Covid-19 pandemic. The Stunting problem in South Tangerang has increased by 5% to 19.8% from 14% in 2021. Therefore, with a qualitative method, we created a stunting prevention program called the AYO CETING (let's prevent stunting) program by holding a group discussion forum (FGD). Implementing the stunting prevention program called AYO CETING (let's prevent stunting), which is carried out, aims to educate the public about how we as women, mothers and parents, can prevent stunting problems. Implementing this program is also a form of community service because it changes the community in the short and long term. This program is carried out by providing education and posters on preventing stunting, such as checking the mother's health during pregnancy and exclusive breastfeeding. In this program, the measure of success can be seen from the community's response in asking and answering questions that have been asked. Several residents were enthusiastic when the education was conducted on stunting prevention.